Study of b-hadron decays to Λ+c h−h′− final states - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2024)
Decays of Ξ −b and Ω−b baryons to Λ+c h−h′− final states, with h−h′− being π−π−, K−π− and K−K− meson pairs, are searched for using data collected with the LHCb detector. The data sample studied corresponds to an integrated luminosity of 8.7 fb−1 of pp collisions collected at centre-of-mass energies √s = 7, 8 and 13 TeV. The products of the relative branching fractions and fragmentation fractions for each signal mode, relative to the B− → Λ+c pπ− mode, are measured, with Ξ −b → Λ+c K−π−, Ξ −b → Λ+c K−K− and Ω−b → Λ+c K−K− decays being observed at over 5 σ significance. The Ξ −b → Λ+c K−π− mode is also used to measure the Ξ −b production asymmetry, which is found to be consistent with zero. In addition, the B− → Λ+c pK− decay is observed for the first time, and its branching fraction is measured relative to that of the B− → Λ+c pπ− mode.